L.I.F.O. OR L.O.F.I.–WHICH? - Blakely, Edward J.; Knutson, Peter H. (The Accounting Review, 1963)
Abstract The article focuses on a procedure followed by practitioners of accounting for the method of inventory determination. The procedure is called dollar-value last in first out (LIFO), may be used to achieve the lowest obtainable final inventory for a manufacturing concern. The dollar-value method was developed in many companies to offset the perpetual inventory limitation of the use of LIFO. The dollar-value method uses a technique of double extension. In this way, ending inventory quantities are extended to two columns, one at current cost, the other at the cost of the base year, the first year that the LIFO method was used. In its effects, LIFO is income statement oriented. As current revenues are realized current cost factors (i.e., costs incurred at the same time as revenues were realized) are deducted immediately from revenues. The net effect is to make the stable monetary unit assumption into more of a reality on the income statement, thus eliminating much of the time lag between costs and revenues during which the value of dollars may change appreciably.